CXCL1 Blockade Improves Murine Aneurysm Healing after Coiling. (16th November 2020) - Patel, Devan; Saengchote, Supreeya; Motwani, Kartik; Dodd, William; Hosaka, Koji; Hoh, Brian L
Abstract: INTRODUCTION: While coiling is often safer than clipping for prophylactic management of intracranial aneurysms, recurrence is a significant concern. Aneurysm healing after coiling is not fully understood, but inflammation appears to play a key role. CXCL1, an inflammatory cytokine, is highly expressed in human aneurysms but its role in aneurysm healing is unknown. METHODS: Carotid artery aneurysms were created in female and male C57BL/6 mice. CXCL1 expression was compared between aneurysms and sham-operated carotid arteries. In a separate cohort, aneurysms were coiled with poly(lactic-co-glycolic acid)(PLGA)-coated coils. Mice received intraperitoneal injections of either CXCL1 neutralizing antibody or IgG control for 7, 14, or 21 days post-coiling. Coiled aneurysms were assessed for aneurysm healing, neutrophil infiltration, macrophage polarization, and total macrophage burden. RESULTS: CXCL1 is highly expressed in murine carotid artery aneurysms. CXCL1 blockade significantly increased aneurysm healing compared to IgG when administered for 14 days (females: 66.4% vs. 51.2%, P = .03; males: 69.8% vs. 47.0%, P = .004) and 21 days (females: 71.9% vs. 45.6%, P = .02; males: 67.8% vs. 53.8%, P = .02), but not when given for only 7 days (females: 48.1% vs. 49.4%, P = .92; males: 52.3% vs. 50.4%, P = 1.00). 14 days of CXCL1 blockade decreased neutrophil infiltration (females: 0.33 vs. 8.58 cells/high power field(hpf), P = .05; males: 0.00 vs. 4.42 cells/hpf, P = .04) and increased reparative M2 macrophages (females: 2.25 vs. 0.79 cells/hpf, P = .03; males: 2.00 vs. 0.27 cells/hpf, P = .02). CONCLUSION: CXCL1 blockade for 14 or 21 days improved aneurysm healing in female and male mice. 14 days of CXCL1 blockade decreased neutrophil infiltration and increased M2 macrophage polarization. A systemic drug such as CXCL1 blockade could be given to patients after coiling to improve aneurysm healing and, consequently, permanent occlusion rates.